Effects of fire on arbuscular mycorrhizal fungi in the Mountain Chaco Forest - Longo, Maria Silvana (2014)
The aim of this study was to evaluate the fire effects on the AMF spore communities and soil chemical properties as well as the existence of possible correlations between them in the Chaco Serrano Forests of central Argentina. Our hypothesis is that the fire has a negative impact on the community of AMF spores (i.e. density, diversity, richness and evenness) and soil chemical properties. In addition, we expect to find a high correlation between changes in the communities of fungi and soil chemical properties. We selected five areas in the "Sierras Pampeanas" mountain ranges within the Chaquean region in central Argentina. In each of them we selected adjacent burned and unburned forest sites. Burned sites have all the same time since fire occurrence (August?November 2009) and soil samples were collected in autumn (April) and spring (November) in 2010. The fire events had direct negative effects on AMF spore communities. Evenness, and notably diversity and richness of AMF spores decreased in the burned sites. Density of AMF spores was not affected by fire. With the exception of C:N, nitrate and electrical conductivity, soil parameters showed significant differences between burned and unburned sites. The changes in AMF spore composition were not significantly correlated with most of the soil variables measured here. The results of this study suggest that fire occurrence negatively affect AMF communities. These effects do not seem to be mediated by changes in soil abiotic properties. Rather, they suggest direct effects of fire on soil fungi.